The effects and Determinants of Training. - Greenhalgh, C; Stewart, M (Department of Economics (University of Warwick), 1982)
Job training is an important subject for discussion, since the skills on which an economy depends are largely created by the process of training. Various theories, especially the human capital model, have focussed attention on skill aquisition through training as a central determinant of individual economic success. What little empirical literature exists on this subject concentrates almost entirely on the effects of individual, government sponsored, special training programmes for those not currently at work. However, the vast majority of training experiences occur whilst the individual is in employment. This study documents the extent of vocational training, taking place both on and off the job, and examines its effects and determinants. The data source is the National Training Survey (NTS) which provides comprehensive details of the training records of more than 50,000 men and women in Great Britain. (For details see Manpower Services Commission, 1976). This data has previously been analysed for men only by Metcalf and Nickell (1982) and by Nickel (1982).